2021
DOI: 10.1038/s41598-021-91147-w
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration in ceramic scaffolds with variable concentrations of PDRN and rhBMP-2

Abstract: This study evaluated the bone regeneration capacity and mechanical properties of block-type hydroxyapatite (HA)/tricalcium phosphate (TCP) scaffolds in response to different concentrations of polydeoxyribonucleotide (PDRN) and recombinant human bone morphogenic protein 2 (rhBMP-2). Thirty-two male white rabbits were used as a model of calvarial bone defect and classified into eight groups according to type and concentration of growth factor administered, viz., control group (only HA/TCP scaffold), scaffold + P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…No disagreement has been reported regarding the positive effect of rhBMP-2 on bone formation; however, the difference in bone formation performance according to the dose of rhBMP-2 is controversial. In several studies, the dose-dependent efficiency of rhBMP-2 carriers has been shown to differ [20,48,49]. However, it was also reported that it is impossible to observe the difference in bone formation according to the concentration of rhBMP-2 [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No disagreement has been reported regarding the positive effect of rhBMP-2 on bone formation; however, the difference in bone formation performance according to the dose of rhBMP-2 is controversial. In several studies, the dose-dependent efficiency of rhBMP-2 carriers has been shown to differ [20,48,49]. However, it was also reported that it is impossible to observe the difference in bone formation according to the concentration of rhBMP-2 [50].…”
Section: Discussionmentioning
confidence: 99%
“…This improves the formation and remodeling of the new bone by providing an appropriate resistance [17]. The use of BCP as a carrier of rhBMP-2 produces good results, and the use of BCP grafts combined with a growth factor may be biocompatible and histologically successful in forming new bones [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al examined the desirable dosage supply of polydeoxyribonucleotide (PDRN) and recombinant human bone morphogenic protein 2 (rhBMP2) to the Hap/TCP scaffold. Bone histomorphometry analysis indicated that PDRN delivery shows no bone growth, while the 0.05 and 0.10 mg/mL delivery of rhBMP-2 resulted in significant bone growth . In a similar study, the osteogenic capability of pure BCP and collagen-added BCP scaffolds were tested with different concentrations of rhBMP-2.…”
Section: Biocompatibility and Bioresorbability Studies On Additive Ma...mentioning
confidence: 98%
“…Bone histomorphometry analysis indicated that PDRN delivery shows no bone growth, while the 0.05 and 0.10 mg/mL delivery of rhBMP-2 resulted in significant bone growth. 258 In a similar study, the osteogenic capability of pure BCP and collagen-added BCP scaffolds were tested with different concentrations of rhBMP-2. Histomorphometry analyses showed that osteogenesis was not enhanced by increasing the concentration of rhBMP-2 in both cases.…”
Section: Biocompatibility and Bioresorbability Studies On Additive Ma...mentioning
confidence: 99%
“…However, bone substitutes cannot be entirely superior to autogenous bone because of the bone morphogenetic proteins (BMPs), which are bone-inducing substances in the natural bone matrix. The addition of growth factors, such as recombinant human bone morphogenetic protein-2 (rhBMP-2) and polydeoxyribonucleotide (PDRN), can improve the biological activity and results [11][12][13][14]. A derivative of bone and cartilage formation, rhBMP-2 was first identified in the 1960s and was approved in 2007 as an alternative to an autogenous bone graft for the maxillary sinus, closure surgery of a cleft palate, and localized alveolar ridge augmentation [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%